An amyotrophic lateral sclerosis-linked mutation in GLE1 alters the cellular pool of human Gle1 functional isoforms. (September 2016) - Aditi; Glass, Laura; Dawson, T. Renee; Wente, Susan R.
Abstract: Amyotrophic lateral sclerosis (ALS) is a lethal late onset motor neuron disease with underlying cellular defects in RNA metabolism. In prior studies, two deleterious heterozygous mutations in the gene encoding human (h)Gle1 were identified in ALS patients. hGle1 is an mRNA processing modulator that requires inositol hexakisphosphate (IP6 ) binding for function. Interestingly, one hGLE1 mutation (c. 1965-2A>C ) results in a novel 88 amino acid C-terminal insertion, generating an altered protein. Like hGle1A, at steady state, the altered protein termed hGle1-IVS14-2A>C is absent from the nuclear envelope rim and localizes to the cytoplasm. hGle1A performs essential cytoplasmic functions in translation and stress granule regulation. Therefore, we speculated that the ALS disease pathology results from altered cellular pools of hGle1 and increased cytoplasmic hGle1 activity. GFP-hGle1-IVS14-2A>C localized to stress granules comparably to GFP-hGle1A, and rescued stress granule defects following siRNA-mediated hGle1 depletion. As described for hGle1A, overexpression of the hGle1-IVS14-2A>C protein also induced formation of larger SGs. Interestingly, hGle1A and the disease associated hGle1-IVS14-2A>C overexpression induced the formation of distinct cytoplasmic protein aggregates that appear similar to those found in neurodegenerative diseases. Strikingly, the ALS-linked hGle1-IVS14-2A>C protein also rescued mRNA export defects upon depletion of endogenous hGle1, acting in a potentially novel bi-functional manner. We conclude that the ALS-linked hGle1-c.1965-2A>C mutation generates a protein isoform capable of both hGle1A- and hGle1B-ascribed functions, and thereby uncoupled from normal mechanisms of hGle1 regulation.